Efektivitas Metode Diskusi dalam Meningkatkan Partisipasi Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Musakal, Musakal; Rosdiana, Rosdiana; Rahman, Agus (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to determine the effectiveness of implementing the discussion method in increasing student learning participation at SD Negeri 8 Mawarangka Timur. The extent to which discussion methods can influence student participation in learning.Method – This type of research is qualitative, where data is obtained through field studies or direct data from original (primary) sources. This research uses primary and secondary data sources. Direct or primary data sources were obtained through informants involving the principal and 3 PAI teachers at SD Negeri 8 Mawasangka Timur. Secondary data was in the form of various journal and book references related to the discussion. Using three data collection methods, namely observation, samples, and interviews. Testing the validity of the data is carried out using the triangulation method or by combining various collection techniques.Findings – The use of the discussion method is quite effective; this can be seen in the final grades obtained from students' Islamic religious education subjects. The highest score obtained by students is 91, the average student score is also around 79 for the first semester and 82 for the first semester. even and absorption capacity in the second semester was 82%, also improving from the previous semester, which increased by 3%. Research Implications – This research illustrates educators that the learning carried out is not just the teacher's responsibility as a profession, namely teaching, but how this learning can be absorbed and understood by students, starting with discussion.